2014
DOI: 10.1097/ico.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endothelial Cell Density of Organ Cultured Corneas With Cornea Donor Study

Abstract: ECD determined by a computer-aided method from transmitted light microscopy images compares favorably with the American CDS reference series. The slight systematic difference on either side of the Atlantic Ocean could be due to (1) differences in counting principles and/or (2) higher shrinkage of the cornea caused by stromal edema in organ culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Other studies have claimed that cause of death has minimal to no significant effect on ECD. 1,2,12 It is important to note that head trauma was not analyzed separately in any of these studies; nonetheless, our results are in accordance with these reports that show that cause of death did not have a statistically significant effect on ECD and that donor age is a more relevant and practical factor in predicting ECD in donor corneas. 1,12 The Cornea Donor Study demonstrated that the decrease in endothelial cell density for each year of increase in donor age was most pronounced in donors less than age 60 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have claimed that cause of death has minimal to no significant effect on ECD. 1,2,12 It is important to note that head trauma was not analyzed separately in any of these studies; nonetheless, our results are in accordance with these reports that show that cause of death did not have a statistically significant effect on ECD and that donor age is a more relevant and practical factor in predicting ECD in donor corneas. 1,12 The Cornea Donor Study demonstrated that the decrease in endothelial cell density for each year of increase in donor age was most pronounced in donors less than age 60 years.…”
Section: Discussionsupporting
confidence: 91%
“…E ndothelial cell density (ECD) is an important criteria used to determine the quality of donor cornea tissue. 1,2 Low endothelial cell count is an important reason for the exclusion of donor grafts from being offered and accepted for corneal transplantation. 3,4 Donor age is negatively correlated with ECD.…”
mentioning
confidence: 99%
“…For the two studies, a total of 100 consecutive patients who underwent PK in our department were enrolled during year 2013. We previously determined the variance of the distribution of ebECD in our European donor population (n=1591 consecutive donors) using the same methods of ebECD counting 10. We calculated that a sample of 100 patients would allow obtaining 95% confident intervals with a ±5% width, which we consider as a reasonable accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…However, measuring ECD in organ culture is limited due to osmotic stress and stromal swelling and consequently endothelial folds due to the presence of dextran and chondroitin sulphate (Campolmi et al. ). Therefore, the three‐dimensional aspect of the stored corneas cannot be taken into account, especially of folds where cell counting results in overestimation caused by parallax error (Gauthier et al.…”
Section: Discussionmentioning
confidence: 99%